Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1021/je3007474
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Pure 1-Butyl-2,3-dimethylimidazolium Tetrafluoroborate Ionic Liquid and Its Binary Mixtures with Dimethyl Sulfoxide and Acetonitrile

Abstract: This work presents density and dynamic viscosity data for the pure ionic liquid, 1-butyl-2,3-dimethylimidazolium tetrafluoroborate, [Bmmim] [BF 4 ], and its binary mixtures with the highly polar solvents dimethylsulfoxide (DMSO) and acetonitrile (ACN), over the entire range of composition and temperatures from (298.15 to 353.15) K at atmospheric pressure. The properties have been represented with temperature by specific equations, both for pure [Bmmim] [BF 4 ] and its binary mixtures. Therefore, an empirical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
38
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 32 publications
(66 reference statements)
8
38
1
Order By: Relevance
“…Ionic liquids (ILs) have been demonstrated to be potential successful replacements for conventional solvents for catalysis and synthesis [1,2] because of their unique physical and chemical properties, including non-volatility, thermal stability, negligible vapor pressure, reusability, and wide electrochemical windows [3]. The ILs can also control miscibility [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Ionic liquids (ILs) have been demonstrated to be potential successful replacements for conventional solvents for catalysis and synthesis [1,2] because of their unique physical and chemical properties, including non-volatility, thermal stability, negligible vapor pressure, reusability, and wide electrochemical windows [3]. The ILs can also control miscibility [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Macedo et al [10] reported the densities, speeds of sound and refractive indices for [BMIM][CF 3 SO 3 ]-water binary mixtures over the whole composition range, at T = (288. 15-308.15) K and atmospheric pressure.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations